Quantifying the benefits of incorporating biochar in green roof substrates: field study on the highrise rooftop in temperate climate setting - Marek Petreje; Michal Sněhota; Václav Šípek; Tereza Hnátková; Jan Punčochář; Stanislav Buchtelík; Michael Hardman; Lukáš Trakal (Biochar)
Abstract Biochar is a promising material with a wide range of applications. One area of application is as an additive in substrates for green roofs. Green roofs are a way of mitigating climate change, with biochar offering an opportunity to further enhance this benefit and upscale practice. In this field study, the effect of a 5-vol.% addition of wood-based biochar to a green roof substrate is evaluated with respect to a water balance (reduced runoff, increased evapotranspiration, increased plant available water) and hydrophysical properties. Substrate, with and without biochar amendment, was used in different green roof sections. Laboratory hydrophysical analysis, in-situ Volumetric Water Content and meteorological measurements, alongside vegetation monitoring, enabled the development of a 1D Hydrus water balance model and revealed differences between both of the surveyed green roofs. The study demonstrated that the addition of biochar to the substrate improved its hydrophysical properties, leading to increased water retention (7.7% increase in maximum water capacity) and enhanced vegetation growth The biochar amendment resulted in the minor changes in grain size distribution (increase in the 0.01 to 0.1 mm fraction) and increased substrate moisture, which is related to an increase in the plant-available water content (14.2%). This was observable in the retention curves and resulted in an increased moisture availability for plants, leading to an increase in vegetation cover in areas with biochar. The numerical analysis using Hydrus-1D soil hydraulic model showed that the inclusion of biochar in the substrate resulted in a 23.5% increase in evapotranspiration and a 54.7% decrease in runoff. These findings suggest that the addition of biochar to the green roof substrate could enhance the system's capacity to retain water, reduce runoff and bulk density, and increase the amount of water available for plant growth. The study provides evidence for the potential of wood-based biochar as a sustainable and effective addition to green roof substrates, contributing to the development of more resilient and sustainable urban environments. Graphical Abstract